Quality of Work Life dan Employee Engagement sebagai Kunci Performance Penyuluh KB di Sulawesi Barat - Said, Padly Hadis; Ramli S, Ramli S; Aqil, Muhammad (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study aims to evaluate the extent to which Quality of Work Life (QWL) and Employee Engagement influence the performance of Family Planning Counselors in West Sulawesi Province. Given their strategic role as the frontline agents in promoting population and family development programs, understanding the key factors that affect their work effectiveness is crucial. Using a quantitative approach, data were collected through questionnaires distributed to 55 active counselors and analyzed using multiple linear regression techniques. The findings reveal that both QWL and employee engagement have a positive and significant impact on counselor performance. When analyzed simultaneously, these two variables accounted for 71.6% of the variance in performance. Interestingly, employee engagement emerged as the more dominant factor compared to QWL. This highlights the critical role of emotional and psychological involvement in fostering dedication and commitment to their responsibilities. These results provide practical implications for policymakers in designing performance improvement strategies that focus on enhancing work environment quality and strengthening employee engagement in a comprehensive manner